2020
DOI: 10.1097/bsd.0000000000001102
|View full text |Cite
|
Sign up to set email alerts
|

Does the Preoperative Depression Affect Clinical Outcomes in Adults With Following Lumbar Fusion?

Abstract: Objective: The objective of this study was to analyze depression using Beck Depression Inventory (BDI) and Hamilton Depression Scale (HAMD-24), and to correlate with clinical outcomes and improvement in adults with following lumbar fusion.Summary of Background Data: Psychological factors such as depression are found to influence outcomes and improvement following spinal surgery. It is still unclear whether there are differences during screening for depression by different implementations to predict outcomes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…One study reported that 73% of patients with cancer who had major depression were not receiving any treatment, 24% were taking antidepressants, and only 5% were seeing a mental health professional [41]. This is important because depression has been shown to correlate with increased pain and disability and worse patient-reported outcomes/satisfaction after nononcologic orthopaedic surgery [4, 18, 37, 39, 46] as well lead to increases in all-cause mortality [16, 17, 31] and higher rates of suicide [23, 33, 45] in patients with cancer. One study looked at suicide rates among people with cancer and found the incidence of suicide to be 31.4 per 100,000 person-years, which is nearly twice as high as the national average of 16.7 per 100,000 person‐years [23].…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that 73% of patients with cancer who had major depression were not receiving any treatment, 24% were taking antidepressants, and only 5% were seeing a mental health professional [41]. This is important because depression has been shown to correlate with increased pain and disability and worse patient-reported outcomes/satisfaction after nononcologic orthopaedic surgery [4, 18, 37, 39, 46] as well lead to increases in all-cause mortality [16, 17, 31] and higher rates of suicide [23, 33, 45] in patients with cancer. One study looked at suicide rates among people with cancer and found the incidence of suicide to be 31.4 per 100,000 person-years, which is nearly twice as high as the national average of 16.7 per 100,000 person‐years [23].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that about 20-40% of the LCS patients have clinically significant depressive symptoms. [7]; and psychological factors importance can also be understandable by the fact that the unrealistic preoperative expectations regarding pain, low optimism and lesser interest in physical activity have poor postoperative clinical outcome [4,7,27,28]. Few studies have also stressed on cognitive-behavioral patient education and role of psychotherapist in improving the clinical as well as quality of life in LCS patients and surgery can be delayed in patients with moderate LCS [7,29].…”
Section: Discussionmentioning
confidence: 99%
“…That number grows substantially when including other mental health disorders such as anxiety, bipolar disorder, and schizophrenia. Patients with a diagnosis of a psychiatric disease have been shown to have worse outcomes after undergoing orthopaedic procedures [27][28][29][30][31][32][33][34][35] . Paradoxically, those with depressive symptoms and low PROMIS-D (depression) scores preoperatively may also demonstrate substantial improvement in depressive symptoms following interventions 29,36,37 , which indicates the impact that musculoskeletal conditions can have on a patient's mental well-being.…”
Section: Mental Health Screeningmentioning
confidence: 99%